Pengaruh Penggunaan Media Loose Parts Terhadap Kemampuan Keaksaraan Anak Usia 5-6 Tahun - Utami, Jayanti Rizki; Amanda, Rizki Surya; Hasni, Uswatul (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This research was motivated by initial observations in the field, which showed that there were several children whose literacy abilities still needed to develop optimally; in particular, those with the most literacy indicators were reading their names and writing their own names. This research aims to determine the effect of using loose part media on the literacy abilities of children aged 5-6 years at the Kembar Lestari Kindergarten, Jambi City. This type of research is quantitative research using experimental methods with a quasi-experimental design. The sample in this study consisted of 30 children. The sampling technique uses purposive sampling. The data collection technique uses a structured observation method with research instruments whose validity has been tested. The data analysis techniques used are normality test, homogeneity test, and hypothesis test. The research results showed that there was a difference in the increase in average scores between the control class and the experimental class. Based on the results of the post-test, it was found that the average score for the experimental class was 3.54 higher than the control class. The results of data analysis using the independent sample t-test show that the probability value Sig. (2-tailed) is 0.000 so that (P = 0.000 < 0.05), by the decision-making provisions, Ho is rejected, and Ha is accepted. Based on the research and discussion results, it was concluded that the use of loose parts media influenced the literacy abilities of children aged 5-6 years at the Kembar Lestari Kindergarten, Jambi City.